Effective judicial protection in consumer litigation : Article 47 of the EU Charter in Practice - Duin, Anna van (Cambridge : Intersentia, 2022)
In EU consumer law, the rise of Article 47 of the EU Charter of Fundamental Rights - which guarantees the right to an effective remedy and a fair trial - over the past decade has coincided with a wave of crisis-induced litigation. Courts were confronted with large numbers of cases against overindebted consumers. This has prompted many questions on the need for effective judicial protection, for instance in mortgage enforcement and order for payment procedures. This book provides a unique perspective on the role of civil courts at the crossroads of EU fundamental rights, consumer law and access to justice. It examines how the Court of Justice of the European Union, as well as civil courts in Spain and the Netherlands, refer to Article 47 in unfair terms cases, where procedural obstacles and inequalities have become particularly visible - especially in Spanish case law. The analysis reveals a divergence between European and national practices and also shows the potential of Article 47, which is often wrongly equated with the principle of effectiveness, in consumer litigation. Effective Judicial Protection in Consumer Litigation makes a vital contribution to the debate on the functions of Article 47 and fundamental rights reasoning in European private law adjudication and is a must read for anyone interested in the application of Article 47 in judicial decision-making.
Title from publisher's bibliographic system (viewed on 18 Nov 2022).
Keywords: Charter of Fundamental Rights of the European Union -- (2000 December 7); Consumer protection -- Law and legislation -- European Union countries; Judicial process -- European Union countries